2000
DOI: 10.1111/j.1445-5994.2000.tb00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximal shift of colorectal cancer in the Australian Capital Territory over 20 years

Abstract: We have detected a number of changes in clinical and pathological aspects of colorectal cancer over a 20 year period in the ACT, including a proximal shift in the subsite distribution of colorectal cancer. These changes suggest that proximal and distal colorectal cancers may have a different aetio-pathogenesis, and have implications for the investigation of patients with suspected colorectal cancer and in screening high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…A change in the epidemiolog y of CRC has been observed in the past decades. Firstly, there was proximal shift of CRC, reported by Axtell and Chiazze [2] and then confirmed by other studies [3][4][5][6][7] . Secondly, there was a change in the mean age of onset of CRC.…”
Section: Introductionsupporting
confidence: 71%
“…A change in the epidemiolog y of CRC has been observed in the past decades. Firstly, there was proximal shift of CRC, reported by Axtell and Chiazze [2] and then confirmed by other studies [3][4][5][6][7] . Secondly, there was a change in the mean age of onset of CRC.…”
Section: Introductionsupporting
confidence: 71%
“…A continued and unequivocal proximal migration is confirmed by the two data sets of the present study. Some authors found that the rightward shift of colon cancer was more pronounced in females, 4,8,9,19 elderly patients, 6,10,11,16 or African Americans. 8,16 Such differences have led to the hypothesis that different genetic and environmental factors could be implicated in the cause of two different cancer types.…”
Section: Discussionmentioning
confidence: 97%
“…Although the United States incidence and mortality of colorectal cancer have declined during the past decades, it still remains the third most common cancer. 1 Many authors have described a change in its anatomic distribution toward the right side, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] whereas others have not seen this trend. [20][21][22][23] The failure of some previous studies to ascertain the relative rise in the occurrence of proximal colon cancer may stem from short observation periods or small study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of proximal tumours in Western countries has steadily increased while that of distal tumours has shown a corresponding decrease. 4,[42][43][44][45][46][47] When populations migrate from low-risk to high-risk areas, the CRC incidence quickly approaches that of the host country, with the largest increase occurring in the distal colon. 48 Taken together, the above geographic, age and gender influences on CRC subsite distribution, in concert with the observations on proximal shift and migrant studies, suggests the existence of 2 broadly different mechanisms of CRC.…”
Section: Epidemiologic Differences In the Incidence Of Right And Leftmentioning
confidence: 99%